2008
DOI: 10.1590/s1517-86922008000500007
|View full text |Cite
|
Sign up to set email alerts
|

Metformina minimiza as alterações morfométricas no músculo sóleo de ratos submetidos à imobilização articular

Abstract: A proposta deste trabalho foi avaliar o músculo sóleo (S) de ratos submetidos à imobilização articular por sete dias, associado ou não ao tratamento com metformina (MET, 1,4mg.ml -1 ) por meio de análises morfométricas. Ratos adultos Wistar (n = 5) foram divididos nos grupos: controle (C), imobilizado em posição neutra do tornozelo (I), tratado com metformina (M), imobilizado tratado com metformina (I + MET). Foram avaliadas a área das fibras, a densidade de área do tecido conjuntivo intramuscular e a massa mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This is consistent with other studies in young adult rodents such that MET was able to reduce fibrosis caused by high fat feeding 25 and limb immobilization. 7 Intramuscular fibroblasts are primarily responsible for collagen and ECM deposition in skeletal muscle. Due to the known coordination of fibroblasts and satellite cells, 21,22 it is possible that the MET + LEUmediated accumulation of satellite cells may have promoted downstream regulation of collagen content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with other studies in young adult rodents such that MET was able to reduce fibrosis caused by high fat feeding 25 and limb immobilization. 7 Intramuscular fibroblasts are primarily responsible for collagen and ECM deposition in skeletal muscle. Due to the known coordination of fibroblasts and satellite cells, 21,22 it is possible that the MET + LEUmediated accumulation of satellite cells may have promoted downstream regulation of collagen content.…”
Section: Discussionmentioning
confidence: 99%
“…1,37 We found that MET + LEU treatment alleviated whole body strength and soleus force loss during disuse and was independent of changes to muscle or fiber size. We were surprised that muscle or fiber size was not altered by the dual treatment, since MET has previously been effective to ameliorate muscle atrophy caused by limb immobilization, 7 high fat feeding 25 and burn injury. 6 Similarly, LEU is a potent stimulator of muscle protein synthesis 11 and, in combination with antioxidant cocktail, was able to prevent disuse-induced muscle atrophy in adult rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GIMP (GNU Image Manipulation Program) 2.0 (GNU General Public License ® , Berkeley, California) program was used to analyse the density of the connective tissue of the endomysium and perimysium (Bosi et al, 2008). The relative area of connective tissue (area density) was calculated by dividing the total number of pixels in the photomicrograph by the total of pixels marking connective tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, research exploring metformin to prevent disuse atrophy and promote muscle recovery in aging at least in rodents appears to be strong. During 7 days hindlimb immobilization in young adult rats, metformin treatment ameliorated muscle atrophy and prevented tissue fibrosis [ 97 ]. In another study, rats treated with metformin during 16 weeks of high fat diet was effective to counter myofiber atrophy, fibrosis and increased E3 ubiquitin ligases expression compared to the non-metformin treated group [ 98 ].…”
Section: Nutritional Therapies Combined With Metforminmentioning
confidence: 99%